An Alternative Approach for Deriving Emission Inventories Solely From Satellite Data: Demonstration for NO2 Over China - Konstantinos Kourtidis; Aristeidis K. Georgoulias; Aristeidis K. Georgoulias (Frontiers in Environmental Science, 2019)
We demonstrate an alternative method for deriving of emission estimates for pollutants using solely columnar satellite data. The method, which we term Lifetime-Modified Accumulation Method (LMAM), does not require any ancillary model run or other data to estimate emissions, but needs only the measured columnar amounts. It employs lifetime calculations from measured daily columnar amounts. The method is applied to nitrogen dioxide over China on a 0.25 × 0.25 and a 1× 1° grid, and emission estimates are derived and compared with a more traditional method. The emission estimates thus derived appear to be consistent with traditional methods, both in their spatial distribution and their magnitude, and correlate well with existing inventories. Ways for refining the method are discussed. The method can be improved, we only wanted to demonstrate here it is feasible to derive inventories solely from satellite data using lifetime calculations.